Color stability of polymer-infiltrated-ceramics compared with lithium disilicate ceramics and composite - Seyidaliyeva, Aida; Rues, Stefan; Hassel, Alexander J.; Rammelsberg, Peter; Zenthöfer, Andreas (Journal of esthetic and restorative dentistry, 2020)
Objective To investigate the color stability of hybrid ceramics and to compare it to composite and lithium disilicate ceramics. Materials and Methods One hundred eighty samples were fabricated and processed with a semiautomatic grinding and polishing device (final step: 1200 grit). After thermocycling, samples were immersed in a staining solution (five subgroups: water, red wine, curry, black tea, cola) for 4 weeks. A spectroradiometer was used to determine the color of the samples in CIE L*a*b*. Color measurements were performed before staining (baseline, initial color), after thermocycling, after 2 and 4 week storage in staining solution and each after a two stage repolishing approach. Discoloration of specimens was calculated by means of ΔE00 compared to baseline values. Results All factors (material, staining solution, aging stage) were significantly associated with the extent of discolorations (P < .001). Maximum color changes occurred after 28 days staining (EN: ΔE00 = 4.5 ± 4.0; GB: ΔE00 = 5.0 ± 4.5; LS: ΔE00 = 3.0 ± 2.3) clearly exceeding the 50:50 threshold for acceptable color deviations. Due to repolishing, discoloration of LS samples was almost completely eliminated (ΔE00 = 0.4 ± 0.3) and significantly reduced for the other two materials (EN: ΔE00 = 1.0 ± 0.9; GB: ΔE00 = 0.9 ± 0.4; P = .428). Conclusion Discoloration of hybrid ceramics ranged in-between lithium disilicate and composites, however more comparable to composites. Repolishing could reduce discolorations substantially. Clinical Relevance This study should help dental practitioners to estimate the color stability of common dental materials and the effect of polishing in removal of discolorations.
First published: 04 October 2019
Gesehen am 27.01.2020